Protection Of Expressions Of Folklore/Traditional Cultural Expressions: To What Extent Is Copyright Law The Solution? - Kuek, Chee Ying (Journal of Malaysian and Comparative Law, 2019)
Folklore forms an integral part of the cultural heritage of a nation and it is an essential means of social identity, particularly for a developing country or certain communities. In recent decades, there has been an increase in the commercial exploitation or appropriation of expressions of folklore (hereinafter referred to as "EoF") or traditional cultural expressions (hereinafter referred to as "TCEs") by entrepreneurs who have no connection whatsover with the communities to which the EoF/TCEs belong. In most cases, the communities who were the custodians or preserves of the EoF/TCEs do not enjoy the economic benefit or share the returns from such unauthorised exploitation by persons not belonging to the communities. Sometimes, very little respect or regard was shown to the custodians of the EoF/TCEs in the commercialisation process in that the EoF/TCEs were used in ways that were insulting, degrading, and/or culturally or spiritually offensive.